A qualitative inquiry into Christian faith transmission in the family context - Holmes, Sarah E. (Practical theology, 2023)
These empirical findings contribute to knowledge regarding Christian faith transmission in the family context, where assumptions are largely un-tested and ideas frequently accepted with minimal critical engagement. The findings presented are part of a three-year empirical research programme comprising in-depth interviews with parents and children in the UK annually, enabling a longitudinal mapping of the child's faith and examination into how family faith activity and involvement may impact it. Play-based interview activities were devised to access authentic and accurate insights into the child's beliefs, perceptions and faith experiences. The data collected was correlated with information about family faith practices and activities to explore potential connections between the two. The 26 case study Christian families revealed fascinating inferences, including that faith discussion in the home is a more significant influence on a child's faith than church attendance, Bible reading or family prayer time. It was striking that the child participants tended to emulate the faith of the parent that they were relationally closest to, reflecting the notion of attachment theory. Some practical implications of these findings are proposed to contribute to the dialogue amidst churches, Christian families and academic contexts regarding how faith may be most effectively transmitted to future generations.